3D image acquisition in scoliosis correction surgery: Radiation exposure of a paediatric patient cohort. (August 2018) - Murphy, Dara; McCoubrey, Siobhan
Abstract : 3D spine imaging has become a popular technique in orthopaedic surgery to assist with the placement of screws and rods for the treatment of scoliosis. It is most often used in combination with navigation software to reduce the risk of surgical-induced patient paralysis. One way to acquire this type of imaging is to use an X-ray c-arm that rotates around the patient, mimicking a cone beam CT acquisition. Although this technique has been successfully implemented in many centres, there is a deficit of information in the literature with regard to the consequent patient radiation exposure, in particular, where an eccentric or non-circular orbit is utilised. This information is particularly important for paediatric patients, as they are the most likely candidates for this type of surgery. Our study estimates the radiation dose to paediatric patients who have undergone scoliosis correction surgery, using the proprietary non-circular orbit employed by a Ziehm Vision RFD 3D C-arm. We estimate and compare patient organ doses using this eccentric orbit with one where a simple circular orbit is assumed. We further compare our calculated organ doses with those imparted by traditional 2D fluoroscopic techniques, and calculate the risk of future radiation induced cancer for this patient cohort. The doses presented here will be useful to other centres in establishing diagnostic reference levels for this increasingly common technique.